Determinants of Public Welfare in Asean's Developing Countries - Andaru, Riza Pahlevi; Saputra, Putu Mahardika Adi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The Human Development Index (HDI), developed by the United Nations Development Programme (UNDP), serves as a key indicator for measuring the well-being of a population. Between 2010 and 2022, HDI levels in eight ASEAN countries experienced notable improvements. However, significant disparities remain among developing nations within the region. This study aims to analyze the factors influencing HDI, namely Gross Domestic Product (GDP), unemployment rate, foreign direct investment (FDI), and exchange rate. The research employs an associative approach using panel data regression analysis on eight developing ASEAN countries Indonesia, Malaysia, Vietnam, Thailand, the Philippines, Myanmar, Laos, and Cambodia over a 13-year period from 2010 to 2022. This is a quantitative study applying the Fixed Effect Model (FEM) approach. The findings indicate that GDP and the unemployment rate have a significant positive impact on human development. In addition, both FDI and the exchange rate also exhibit a significant positive influence on HDI. These results highlight the importance of macroeconomic and investment-related factors in promoting human development across developing ASEAN economies.